Experimental Investigation on Physio-Mechanical and Micro-Structural Properties of fly ash based Geopolymer Concrete made by replacing fine aggregate with coal bottom ash - Zewdu, Sileshi (ASTU, 2023)
The demand for concrete as a material for construction will increase as the need for infrastructure development increases. Such an enormous utilization of concrete in the construction sector calls for a higher use of cement and natural aggregates. Fly ash based geopolymer concrete has a potential to enhance the sustainability of concrete product. Most previous works examined the properties of fly ash-based geopolymer concrete (GPC) subjected to curing at elevated temperatures, and there is lack of knowledge on geopolymer concrete incorporating coal bottom ash replacing fine aggregate. Therefore, the current study aimed to investigate the physio-mechanical, micro-structural properties, and environmental impacts of fly ash-based geopolymer concrete with bottom ash replacing fine aggregate. In this study, the characterization tests for fly ash and bottom ash, compressive strength, flexural strength, water absorption, and microstructural properties of the hardened geopolymer concrete were investigated. To make geopolymer concrete, fly ash and bottom ash, natural river sand, coarse aggregate, NaOH (16 M) flakes, and Na2SiO3 liquids with the ratio of NaSiO3/NaOH =2, were mixed together. The replacement of sand with bottom ash was 0%, 5%, 10%, and 15% by weight. From this test result, Due to the viscous nature of alkaline activators as well as the increased water absorption and surface texture of bottom ash, the workability of the concrete decreased as the amount of bottom ash in the geopolymer concrete mix increased. The compressive strength of concrete was improved by 1.03% for 5% replacement at the age of 28 days as compared to the control sample; however, it decreased between 10 and 15%. In addition, the result has shown a comparable flexural strength between the geopolymer concrete at 5% sand replacement scenario and conventional concrete. Furthermore, the water absorption of the concrete increased as the percentage of replacement increased because of the porous surface of the bottom ash. Hence, from the study, generally a geopolymer concrete of C-25 with acceptable physio-mechanical properties can be produced. while reducing the environmental impact of cement manufacturing, and industrial by-products
Keywords: geopolymer concrete; ambient curing; fly ash; bottom ash; alkaline activator